From Paddles to Engines: Modernization, Social Capital, and Adaptive Strategies of Bajo Sea Nomads in Coastal Southeast Sulawesi - Pendais Hak; Abdul Sakti; Khabiirun Khabiirun; Alimin Alwi (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The Bajo community of Pulau Saponda, Southeast Sulawesi, Indonesia, is one of Southeast Asia’s most prominent sea-nomad societies. Since the late 1980s, the transition from paddle-and-sail boats to motorized vessels has transformed fishing practices, market access, and social organization. However, the role of social capital and local institutions in shaping adaptation to fishery modernization remains insufficiently understood. Objectives: This study examines the impacts of fishery modernization on the Bajo community and explores the ecological, socio-cultural, and economic strategies developed to adapt to these changes. Methods: A qualitative ethnographic approach was employed. Fieldwork was conducted in June 2020 with five purposively selected male informants representing diverse fishing activities and generational experiences. Data were collected through in-depth interviews, participant observation, and field notes, then analyzed thematically using established qualitative procedures. Results: Motorization expanded fishing ranges, reduced travel time, improved market integration, and increased productivity, while also reinforcing socioeconomic inequalities between vessel owners. Social capital, expressed through mutual aid, inter-household networks, and informal patron-client credit arrangements, remained central to community resilience but provided limited access to external institutions. Adaptive strategies included shifting fishing grounds, aquaculture, livelihood diversification, educational investment, knowledge exchange, and participation in conservation initiatives. Modernization also contributed to the decline of traditional practices, oral traditions, and communal labor systems. Conclusion: Fishery modernization has simultaneously enhanced economic opportunities and intensified social differentiation. Although strong bonding social capital supports resilience, limited bridging connections constrain broader development opportunities. Strengthening microfinance access, community-based fisheries governance, and cultural preservation programs may improve both livelihood sustainability and cultural resilience. Keywords: Bajo people; fishery modernization; social capital; adaptive strategies; livelihood diversification